2011
DOI: 10.1063/1.3656739
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of hydrogen permeation in palladium-gold alloys

Abstract: Density functional theory and lattice model calculations are combined to study the permeability of hydrogen in Pd lightly alloyed with Au. This study shows that small amounts of Au substitutions in Pd leads to, respectively, an increase and decrease of the diffusivity and solubility of hydrogen in the alloy. The competition between these two phenomena depends on temperature and can yield dilute PdAu membranes with a hydrogen permeability higher than pure Pd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The significant variation in grain size in the dehydrated samples (Figures 6, 7 and 9d) and the inclusions of olivine and enstatite in coarse-grained olivine (Figure 7) strongly demonstrate that significant grain growth should have occurred after the nucleation. The CPOs of fine-grained olivine in our study (Figures 8 and S3) are consistent with those of prograde olivine and enstatite reported in Padrón-Navarta et al ( 2015 Padrón-Navarta et al (2015), the sealed capsules were made of Au that is not permeable for H (Xu et al, 2011). Hence, the antigorite was dehydrated under an undrained condition.…”
Section: Olivine Cpo Evolution During Antigorite Hydrostatic Dehydrationsupporting
confidence: 91%
See 2 more Smart Citations
“…The significant variation in grain size in the dehydrated samples (Figures 6, 7 and 9d) and the inclusions of olivine and enstatite in coarse-grained olivine (Figure 7) strongly demonstrate that significant grain growth should have occurred after the nucleation. The CPOs of fine-grained olivine in our study (Figures 8 and S3) are consistent with those of prograde olivine and enstatite reported in Padrón-Navarta et al ( 2015 Padrón-Navarta et al (2015), the sealed capsules were made of Au that is not permeable for H (Xu et al, 2011). Hence, the antigorite was dehydrated under an undrained condition.…”
Section: Olivine Cpo Evolution During Antigorite Hydrostatic Dehydrationsupporting
confidence: 91%
“…In the experiments performed by Padrón‐Navarta et al. (2015), the sealed capsules were made of Au that is not permeable for H (Xu et al., 2011). Hence, the antigorite was dehydrated under an undrained condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(iii) For a Pd-Au alloy, the theory was used to scrutinize the arrangement of atoms [20][21][22][23][24]. In addition, DFT indicates that hydrogen absorption becomes less favorable with increasing Au content [25,26]. Detailed tables with the binding energies and frequencies of vibrations of H atoms for H absorption on sites with different arrangements of Pd and Au atoms are, however, lacking there, and accordingly the use of the data reported was not straightforward in our context.…”
Section: Introductionmentioning
confidence: 99%
“…2 is 0.54 eV (Fig 1(a)). In the bulk of Pd, hydrogen finds stable configurations in correspondence of the octahedral (O h ) and tetrahedral (T d ) sites of the fcc lattice [22]. Our calculations give, in particular, energies of -0.02 eV and 0 eV for a hydrogen species in Pd at the O h and T d sites, respectively.…”
Section: Resultsmentioning
confidence: 88%